2018
DOI: 10.1029/2018wr022704
|View full text |Cite
|
Sign up to set email alerts
|

Evapotranspiration Trends (1979–2015) in the Central Valley of California, USA: Contrasting Tendencies During 1981–2007

Abstract: Trends in monthly evapotranspiration (ET) rates across three watersheds covering the Central Valley in California were calculated by the latest calibration‐free version of the complementary relationship of evaporation for 1979–2015. While a recent study concluded that ET rates of the irrigated fields in the Central Valley were declining in 1981–2007, here an ET trend of about 2.6 ± 12 mm per decade was found over the same period in spite of a drop in precipitation (−22 ± 30 mm per decade) and ET rates (−9.5 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 60 publications
1
22
0
Order By: Relevance
“…On the other hand, a new and independent study of evaporation across the irrigated crops of the Central Valley, using Morton's complementary evaporation method (Morton, ), estimates that annual evaporation is on the order of 369 ± 62 mm/year (Szilagyi & Jozsa, ), which is close to our calculations. It is also consistent with regional estimates of evaporation across the Central Valley computed with GLDAS (406 ± 50 mm/year) and SSEB (489 ± 51 mm/year; see Supporting Information Figures S10, S11, and S12).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…On the other hand, a new and independent study of evaporation across the irrigated crops of the Central Valley, using Morton's complementary evaporation method (Morton, ), estimates that annual evaporation is on the order of 369 ± 62 mm/year (Szilagyi & Jozsa, ), which is close to our calculations. It is also consistent with regional estimates of evaporation across the Central Valley computed with GLDAS (406 ± 50 mm/year) and SSEB (489 ± 51 mm/year; see Supporting Information Figures S10, S11, and S12).…”
Section: Discussionsupporting
confidence: 86%
“…Typically, they are averaged over many years, to minimize errors due to changes in storage (Dralle et al, 2018;Draper et al, 2003). Others have focused on the evaporation from agricultural regions of the State (Burt et al, 2002;Sorooshian et al, 2011;Szilagyi & Jozsa, 2018).…”
Section: Water Resources Researchmentioning
confidence: 99%
“…Szilagyi and Schepers () demonstrated that the wet surface temperature is independent of areal extent, thus T wes can be obtained from the Bowen ratio of a small wet patch for which the Penman equation is valid, that is, βwe=RnGETpitalicETnormalpγTwesTaenormalo,italicTwesea, in which β we is the Bowen ratio of the well‐watered patch (assuming that available energy for the wet patch is close to that of the drying surface), e o, T wes being the saturated vapor pressure at T wes (≈ T wea ). Note that T wes may be larger than T a when the air is close to saturation, and in such cases, T wea should be capped by T a (Szilagyi, ; Szilagyi & Jozsa, ). α in equation is the dimensionless Priestley‐Taylor coefficient, with typical values from the range of [1.1–1.32] (Morton, ).…”
Section: Methodsmentioning
confidence: 99%
“…in which β we is the Bowen ratio of the well-watered patch (assuming that available energy for the wet patch is close to that of the drying surface), e o,Twes being the saturated vapor pressure at T wes (≈T wea ). Note that T wes may be larger than T a when the air is close to saturation, and in such cases, T wea should be capped by T a (Szilagyi, 2014;Szilagyi & Jozsa, 2018). α in equation (6) is the dimensionless Priestley-Taylor coefficient, with typical values from the range of [1.1-1.32] (Morton, 1983).…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation